Lignite in Polish State Policies as a Regulatory Instrument - Hubert Schwarz; Zbigniew Kasztelewicz; Anna Nowak-Szpak (Energies)
Poland is a country with significant lignite resources. Prospecting for and exploring lignite deposits, as well as lignite extraction, requires prior acquisition of an appropriate concession. As concessions serve as instruments for regulating economic activity—and thereby constitute a form of permissible restriction on such activity under the Polish Constitution—the legal provisions governing them must be enacted by statute. This article analyzes the role of state policies relating to lignite extraction and its use in electricity generation, and examines the concession procedure as a regulatory instrument, with a particular focus on one specific ground for refusing to grant a concession: inconsistency with the state’s raw material interest. The main research question addresses whether the incorporation of the state’s raw material interest as grounds for refusal complies with constitutional standards and whether policy documents—specifically the State Raw Materials Policy and the State Energy Policy—can effectively guide its interpretation. The analysis concludes that, while the constitutional framework permits such a ground for refusal, current policy documents require updates and greater specificity to ensure legal certainty and consistency in administrative practices.